The composition of leading organs of the CPSU (1952-1976). CPSU CC Politburo and secretartiat members. CPSU CC full and candidate members. CPSU Central Auditing Commission members. (As of September 1, 1976). Comp. by H. Kraus (N.pl., 1976)
Supplement to the Radio Liberty Research Bulletin.